Strategies to Increase Student Awareness of Negative Content (Tik Tok) in the Digital Era: A Case Study of SMPN 2 Sakra Timur - Azizah Wiza Aratul; Rido Januar Hadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to develop effective strategies to increase students' awareness of negative content on the TikTok platform, focusing on students at SMPN 2 Sakra Timur. In today's digital era, the use of social media, particularly TikTok, has become an integral part of students' daily lives. However, inappropriate and potentially harmful content can affect students' character development and behavior. Through a qualitative approach, this study identified various types of negative content frequently accessed by students and their impact on their behavior. Furthermore, this study explored the role of teachers and parents in providing appropriate media education. The results of this study indicate that increased awareness can be achieved through educational programs involving interactive discussions, digital literacy training, and collaboration between schools and parents. By implementing these strategies, it is hoped that students will be more critical in filtering the content they consume, thereby minimizing the negative impacts of TikTok and other social media use. This research is expected to serve as a reference for other schools in addressing similar challenges in the digital era.